PENGARUH KUALITAS LAYANAN TERHADAP KEPUTUSAN MEMINJAM DANA ONLINE (Studi Kasus Pada Mahasiswa di Universitas Islam Malang) - Devi Nabila Wahyu Dwi Wulandari; M Hufron; Siti Asiyah (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT This research aims to identify and analyze the quality of services consisting of (physical evidence, reliability, responsiveness, assurance, empathy) to the decision to borrow online funds on Kredivo both simultaneously and partially, and to know which variables are the most dominant. This study uses quantitative research types. The population in this research is a user of the online funds loan service Kredivo. Samples taken as many as 100 respondents. The sampling technique used is non probability sampling. Data was analyzed using multiple linear regression analyses treated with SPSS 16.0 software. The data collection method is a questionnaire. The results of the study showed that the quality of service consisting of (physical evidence, reliability, responsiveness, assurance, empathy) was simultaneously and partially influential in the consumer's decision to borrow online funds on Kredivo, and the dominant influential variable physical evidence of consumer decision-making online funds on Kredivo, while the reliability of significant negative influence on consumer decisions was made online funds on Kredivo.Keywords: quality of service, online loan funds